Optimized fertilizer–microbe ratios enhance synergistic restoration of alpine mining ecosystems - Cai, Zongcheng; Shi, Jianjun; Fu, Shouquan; Li, Fayi; Lv, Liangyu; Liu, Qingqing; Zhang, Hairong; Bao, Shancun (Frontiers in Microbiology, 2025)
IntroductionTo address the critical issues of soil fertility depletion, poor vegetation establishment, and functional degradation of microbial communities in degraded alpine mining ecosystems, this study focuses on the Muli coal mine on the Qinghai–Tibet Plateau. This study systematically examined the synergistic regulatory mechanisms underlying the combined application of compound microbial inoculants and forage-specific fertilizers for restoring degraded ecosystems. The findings establish a theoretical framework and technical approach for rehabilitating fragile alpine ecosystems under extreme environmental conditions.MethodsA three-year field experiment was conducted using a long-term plot design. Integrated assessments of vegetation performance, soil physicochemical properties, and soil bacterial community structure (via high-throughput 16S rRNA gene sequencing) were performed. Multivariate statistical analyses, including redundancy analysis (RDA) and structural equation modeling (SEM), were employed to evaluate the comprehensive effects of fertilizer–microbe co-application on the vegetation–soil–microorganism system.Results and discussionThe optimized fertilizer–microbe treatment (W3J1: 375.00 kg·hm−2 forage-specific fertilizer + 350.00 kg·hm−2 compound microbial inoculant) significantly promoted vegetation growth, increased soil carbon and nitrogen contents, and effectively alleviated soil salinization. This treatment reshaped soil bacterial community structure, enriched functional taxa (e.g., Pseudomonadota and Bacteroidota), and enhanced the complexity and functional potential of microbial interaction networks. Mechanistic analysis revealed that the synergistic effect of fertilizer and microbes primarily drove ecosystem recovery through a dual-pathway mechanism: direct microbial regulation and vegetation–soil feedback. The direct effect on bacterial α-diversity was extremely significant (β = 0.76, p < 0.001). Soil pH was identified as the key driver of microbial community assembly, while excessive fertilization induced salinity rebound, indicating a clear application threshold. This study provides a theoretical basis and technical support for the precise ecological restoration of fragile ecosystems in alpine mining areas.